Pengaruh Kemampuan Kerja dan Keterlibatan Kerja terhadap Organizational Citizenship Behavior dengan Tanggung Jawab sebagai Variabel Mediasi pada Pegawai Puskesmas Mempawah Hilir Kalimantan Barat - Nadira Aqilla Adzra; Rian Andriani; Yen Efawati (ManBiz: Journal of Management and Business, 2025)
Organizational dynamics in today's workplace require employees not only to perform their core duties but also to undertake extra tasks beyond their responsibilities. This behavior is known as organizational citizenship behavior, a voluntary behavior that goes beyond formal obligations but has a positive impact on teamwork and organizational effectiveness. Work ability, work engagement, and responsibility are factors that drive organizational citizenship behavior. Employees with high work ability and work engagement will be responsible for their tasks and work. This study aims to determine and analyze the influence of work ability and work engagement on organizational citizenship behavior with responsibility as a mediating variable among employees at Puskesmas Mempawah Hilir Kalimantan Barat. The study population consisted of 55 individuals, comprising a sample size of 55 individuals. This quantitative study employed a causal descriptive approach and was analyzed using outer and inner model tests, hypothesis testing, and mediation analysis with Smart PLS. The result show that work ability has a positive and significant effect on responsibility, work ability has a negative but significant effect on organizational citizenship behavior, work ability has a positive and significant effect on organizational citizenship behavior mediated by responsibility, work engagement has a positive and significant effect on responsibility, work engagement has a positive and significant effect on organizational citizenship behavior, work engagement has a positive and significant effect on organizational citizenship behavior mediated by responsibility, and work ability and work engagement simultaneously have a positive and significant effect on organizational citizenship behavior mediated by responsibility.